Endoscopic Management Using Novel Haemostatic Agents for Immediate Bleeding during Endoscopic Retrograde Cholangio-Pancreatography - Cosmas Rinaldi Adithya Lesmana; Sharon Sandra; Maria Satya Paramitha; Rino Alvani Gani; Laurentius A. Lesmana (Canadian Journal of Gastroenterology and Hepatology)
Bleeding after endoscopic sphincterotomy (ES) remains as a major challenge during ERCP procedure. Standard endoscopic haemostatic procedures have demonstrated good performance for bleeding control. Novel endoscopic haemostatic agents have also been widely used in gastrointestinal bleeding management. Regardless, there is still a paucity of high-quality evidence evaluating the practicality of these agents in ERCP. This case series study was performed on the patients who underwent ERCP procedure in a tertiary referral private hospital within 2 years period. Post-ES immediate bleeding is defined as the onset of bleeding at the time of sphincterotomy. Treatment groups for post-ES bleeding are divided into (1) standard haemostatic methods and (2) novel haemostatic agents. There were 40 patients who received standard haemostatic treatment and 60 patients who received novel haemostatic agents. Initial haemostasis was achieved in all patients. Two patients who received standard haemostatic treatment had rebleeding. Meanwhile, no patients in novel haemostatic treatment group had rebleeding. In conclusion, novel haemostatic agent can be considered as an easy and practical method in daily practice, especially when an ERCP procedure is performed. Further studies with larger sample size which, if possible, can also include a cost-effectiveness analysis are still required to implement these agents as a standard procedure in clinical practice. (This abstract has been presented at the American College of Gastroenterology meeting October 2021).